العنف السياسي في رواية طيور التاجي لإسماعيل فهد اسماعيل - العبودي, ضياء غني (University of El-oued, 2020)
ملخص: حفلت الرواية العربية بصور شتى عن العنف الذي عصف في العالم العربي ، كالقتل والتهجير والاحتقان الطائفي ، وقد عالجت الرواية العربية هذه الظاهرة في كثير من الأعمال من بينها رواية (طيور التاجي) للروائي إسماعيل فهد إسماعيل، التي سنقف عند تمثلات العنف فيها وتحديدا العنف السياسي.من موت وسجن وقمع فضلا عن الموت المعنوي الذي جسده فقدان الهوية والانتماء عند فئة ما يعرف بالبدون والحصار الاقتصادي الذي فرض على العراق ، بطريقة سردية مغايرة جعلت الروائي يقف على مسافة واحدة من الشعبين الكويتي والعراقي ، اللذين تعرضا للظلم نفسه ، محاولا الإجابة عن سؤال كيف عرضت الرواية العنف ، وما صوره ، وكيف وقفت على مسافة واحدة في أحداثها ؟ Abstract The Arabic novel was filled with various images of violence that struck the Arab world, such as killing, displacement and sectarian congestion, and the Arab novel dealt with this phenomenon in many works, including the novel (Birds of Taji) by the novelist Ismail Fahd Ismail, which we will stand at the representations of violence, specifically political violence. From death, imprisonment, and repression as well as the moral death that was embodied by the loss of identity and belonging at the category of what is known as the Bidoon and the economic blockade imposed on Iraq, in a different narrative way that made the novelist stand at the same distance from the Kuwaiti and Iraqi peoples, who were subjected to the same injustice, trying to answer the question of how it was presentedThe novel, violence, and its forms, and how it stood at the same distance in its events?
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج03. ع.02. جامعة الوادي
Keywords: العنف ; السياسة ; السجن ; الحرب